A QUASI-EXPERIMENTAL EXAMINATION OF LEARNING STYLE-BASED ENGLISH INSTRUCTION AND ITS INFLUENCE ON ACADEMIC SUCCESS - Seddik, Mahmoud (International Journal of Language and Literary Studies, 2025)
This study explores whether matching English language instruction to students' preferred learning styles affects their performance in language tasks. Using a quantitative quasi-experimental design, two student groups were compared: one received instruction customized to their learning style preferences, while the other followed a standard, non-customized curriculum. Over eight weeks, participants were evaluated on tasks targeting listening, speaking, and writing skills. Although learning style theories are widely embraced in education, the study found no statistically significant differences in performance between the two groups. Both sets of students achieved similar results, suggesting that aligning teaching methods with learning styles did not improve outcomes. These findings question the belief that tailoring instruction to individual preferences enhances learning. The study underscores the need for evidence-based teaching methods and recommends adopting flexible, adaptive instructional strategies that apply universally effective principles to support all learners, regardless of learning style.